Design of the DOVE (Determining Effects of Platelet Inhibition on Vaso‐Occlusive Events) trial: A global Phase 3 double‐blind, randomized, placebo‐controlled, multicenter study of the efficacy and safety of prasugrel in pediatric patients with sickle cell anemia utilizing a dose titration strategy. Issue 2 (24th September 2015) - Hoppe, Carolyn C.; Styles, Lori; Heath, Lori E.; Zhou, Chunmei; Jakubowski, Joseph A.; Winters, Kenneth J.; Brown, Patricia B.; Rees, David C.; Heeney, Matthew M.
Abstract : Background: Sickle cell disease (SCD) is an inherited blood disorder characterized by painful vaso‐occlusive crises (VOC) with limited treatment options, particularly for children. Emerging knowledge of the pathophysiology of SCD suggests antiplatelet therapies may hold promise for treatment of VOC. Multiple small studies have evaluated antiplatelet agents on the frequency of VOC with varying results, but there has not been an adequately powered study to definitively determine the effect of antiplatelet agents on VOC. Prasugrel, a third‐generation thienopyridine that irreversibly inhibits platelet activation and aggregation, is approved in adults with acute coronary syndrome managed with percutaneous coronary intervention. Procedure: D etermining Effectso f Platelet Inhibition onV aso‐OcclusiveE vents (DOVE) is a double‐blind, randomized study with planned enrollment of >220 children from 14 countries across the Americas, Europe, Asia, and Africa, designed to test the hypothesis that prasugrel reduces the rate of VOC in children with sickle cell anemia (SCA) (homozygous hemoglobin S [HbSS] and hemoglobin Sβ 0 thalassemia [HbSβ 0 ]). Secondary study endpoints include reductions in rate and intensity of vaso‐occlusive pain as recorded in daily electronic diaries. Safety assessments include incidence of hemorrhagic events requiring medical intervention and treatment‐emergent adverse events. DOVE incorporates a dose‐titration strategy to reduce potential bleeding risks inherent with antiplatelet therapy while maintaining blinded treatment assignment. Conclusions: DOVE presents a unique opportunity to determine whether antiplatelet therapy reduces frequency of patient‐reported VOC and daily vaso‐occlusive pain in a global study of children with SCA. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.